Composition of Ileal Bacterial Community in Grazing Goats Varies across Non-rumination, Transition and Rumination Stages of Life - Jiao, Jinzhen; Wu, Jian; Zhou, Chuanshe; Tang, Shaoxun; Wang, Min; Tan, Zhiliang (Frontiers in Microbiology, 2016)
The establishment of gut microbiota is increasingly recognized as a crucial action in neonatal development, host health and productivity. We hypothesized that the ileal microbiome shifted as goats matured, and this colonization process would be associated with host fermentation capacity. To this end, eighteen Liuyang black grazing goats were randomly slaughtered at d 0, 7, 28, 42 and 70. Ileal microbiota was profiled by Miseq sequencing of 16S rRNA gene of bacteria, and fermentation capacity [volatile fatty acid, activities of amylase, carboxymethylcellulase (CMCase) and xylanase] was determined using digesta sample. Principal coordinate analysis (PCoA) revealed that each age group harboured its distinct bacteria. Total bacteria copy number and most alpha diversity indexes increased (P < 0.01) from d 0 to 70. At the phylum level, abundances of Cyanobacteria (P = 0.018) and TM7 (P = 0.010) increased linearly, abundances of Bacteroidetes (P = 0.075) and Fibrobacteres (P = 0.076) tended to increase linearly, whist Proteobacteria abundance tended to decline quadratically (P = 0.052) with age. At the genus level, Enterococcus (30.9%), Lactobacillus (32.8%) and Escherichia (2.0%) dominated at d 0, while Prevotella, Butyrivibrio, Ruminococcus, SMB53 and Fibrobacter surged in abundance after d 20. The highest amylase activity was observed at d 42, while xylanase activity increased quadratically (P = 0.002) from d 28 to 70. Correlation analysis indicated that abundances of Bacteroides, Clostridium, Lactobacillus, Propionibacterium, Enterococcus and p-75-a5 positively correlated with enzyme activity. Collectively, ileal bacteria in grazing goats assemble into distinct communities throughout development, and might participate in the improvement of host fermentation capacity.